'I expected just to walk in, get my tablets and then walk out': on framing new community pharmacy services in the English healthcare system. Issue 6 (19th April 2018) - Latif, Asam; Waring, Justin; Watmough, Deborah; Boyd, Matthew J.; Elliott, Rachel A.
Abstract: Reconfiguration of the healthcare division of labour is becoming increasingly attractive in the context of increased patient demand and resource constraints. One example is the introduction of extended roles for pharmacists to provide patients additional support to manage their medicines, while also reducing work pressures experienced by other health professionals. Understanding how such policies are framed by those delivering and receiving care has been under‐theorised. Using Goffman's frame theory, we examine one newly introduced community pharmacy service (New Medicines Service (NMS)) to illustrate how a policy intended to support patient medicine‐taking through the extended roles of pharmacists is framed and where this deviates from its proposed aims. Three themes emerged: (i) the spatial‐material artefacts; (ii) existing discursive culture and practice around medicine‐taking; and (iii) the NMS interactions that shape and govern framing and subsequent interpretation of the NMS. Our study offers an explanatory and dynamic view of the framing process with important lessons for reconfiguring medicine management policy and practice. As well as illustrating framing as being variegated, complementary or conflicting, it also shows how this plurality and fragility had consequences for patient engagement and sense‐making. The consequences for engagement and recommendations for implementing future initiatives are discussed.